2020
DOI: 10.1186/s12893-019-0669-3
|View full text |Cite
|
Sign up to set email alerts
|

The application of enhanced recovery after surgery for upper gastrointestinal surgery: Meta-analysis

Abstract: Background: Although enhanced recovery after surgery (ERAS) has made great progress in the field of surgery, the guidelines point to the lack of high-quality evidence in upper gastrointestinal surgery. Methods: Randomized controlled trials in four electronic databases that involved ERAS protocols for upper gastrointestinal surgery were searched through December 12, 2018. The primary endpoints were lung infection, urinary tract infection, surgical site infection, postoperative anastomotic leakage and ileus. The… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 54 publications
1
25
0
1
Order By: Relevance
“…On the other hand, it accelerates the fast recovery and early discharge. 25,47,48 The dosage of remifentanil, intraoperative sufentanil and postoperative sufentanil in Group Q were significantly less than Group C, respectively (P<0.05), indicating that QLB preemptive analgesia can significantly reduce postoperative pain, which is consistent with the results of Kadam et al 49 In a systematic review and meta-analysis, Korgvee et al 50 revealed that QLB could reduce postoperative opioid consumption and prolonged the time to the first rescue opioid analgesic after abdominal and hip surgery. Surgical factors, residual anesthetics and postoperative analgesics may cause adverse reactions such as drowsiness, nausea, and vomiting.…”
Section: Discussionsupporting
confidence: 60%
“…On the other hand, it accelerates the fast recovery and early discharge. 25,47,48 The dosage of remifentanil, intraoperative sufentanil and postoperative sufentanil in Group Q were significantly less than Group C, respectively (P<0.05), indicating that QLB preemptive analgesia can significantly reduce postoperative pain, which is consistent with the results of Kadam et al 49 In a systematic review and meta-analysis, Korgvee et al 50 revealed that QLB could reduce postoperative opioid consumption and prolonged the time to the first rescue opioid analgesic after abdominal and hip surgery. Surgical factors, residual anesthetics and postoperative analgesics may cause adverse reactions such as drowsiness, nausea, and vomiting.…”
Section: Discussionsupporting
confidence: 60%
“…Currently, more generalized perioperative care programs are being studied and implemented in the form of ERAS protocols. 62 As part of the ERAS protocols, lifestyle interventions (e.g., alcohol cessation) are introduced in daily practice. 63 – 65 In addition, there is more focus on preoperative malnutrition and impaired physical capacity, which are shown to be negative prognostic factors for postoperative complications in this meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced recovery after surgery (ERAS) was first reported by a Danish surgeon Kehlet, and it was successfully applied in the elective surgery of colorectal tumor [ 5 ]. ERAS organically combining new techniques in anesthesiology, pain management, nutritional support, and surgery with improved traditional postoperative care aims to reduce or alleviate perioperative traumatic stress, promote postoperative recovery of intestinal function, facilitate postoperative rehabilitation, shorten length of stay, and lower medical expenses through multidisciplinary collaboration [ 6 , 7 ]. In the present study, the effectiveness and safety of ERAS in total laparoscopic radical gastrectomy were assessed.…”
Section: Introductionmentioning
confidence: 99%